"Living together with dementia": preliminary results of a training programme for family caregivers - Sousa, Lia (2020)
The aim of this article was to present the preliminar results of a training programme for family caregivers of people with dementia at an early to moderate stage living at home – ‘Living Together With Dementia’. In this randomised controlled trial, 27 family caregivers who met the inclusion criteria were recruited from the neurology outpatient consultation clinic of a hospital in the north of Portugal and randomised into two groups (control and experimental) between October 2015 and March 2016. The programme ‘Living Together With Dementia’ was applied to the participants of the experimental group. The strategies used, overload, difficulties and satisfaction of the caregivers were assessed at three different stages (at the beginning and end of the intervention, as well as at follow-up). For the data analysis, quantitative parametric measures were applied. The Health Ethical Commission of the Hospital Centre approved the study, and its protocol and Helsinki Declaration ethical principles were considered throughout the process. In the final assessment, an improvement in the overload and difficulties was confirmed, as was an increase in the caregivers’ satisfaction level and an improvement in coping/problem-solving strategies. In the follow-up stage, the results tended to revert towards those of the initial assessment. The programme ‘Living Together With Dementia’ appeared to be a major contribution enabling family caregivers of people with dementia, although there is a need to develop an efficacy study using a more substantial sample. The programme contributed to a reduction in the overload and difficulties borne by the family caregivers of people with dementia at an early to moderate stag